Application of agar liquid-gel transition in cultivation and harvesting of microalgae for biodiesel production. (November 2017) - Kumar, Vinod; Nanda, Manisha; Verma, Monu
Graphical abstract: Highlights: Microalgal cells are seeded in the agar medium in four different concentrations. No difference in growth rate and biochemical contents of agar and control media. Microalgae grow within the agar gel in clusters rather than individual cells. Microalgal clusters gravimetrically settle at the bottom in 2 h. In this method agar can be reused. Abstract: In order to increase microalgal biomass productivity efficient cultivation and harvesting methods are needed against the available traditional methods. The present study focuses on the same by harvesting microalgae using agar gel. Agar medium containing bold's basal medium (BBM) undergoes a thermoreversible gel transition. As compared to the traditional protocols, this gel is used to cultivate microalgae without even affecting the total productivity. To develop the gel for microalgae cultivation, agar was boiled in BBM. Then the agar was cooled to 35 °C and microalgae culture was added to it. After seeding the microalgae the temperature of the agar was further decreased by 10 °C to induce gelation. Instead of isolated cells microalgae were grown in clusters within the agar gel. Microalgal clusters gravimetrically settle at the bottom within 2 h. In this method agar can be reused.